2009
DOI: 10.2143/ac.64.3.2038027
|View full text |Cite
|
Sign up to set email alerts
|

CTSS promoter -25G/A: not a risk factor for CHD in Chinese

Abstract: The CTSS -25G/A polymorphism was not related with CHD in our Chinese population sample.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…It was also found that the (h02) C spots with h = odd remain stronger than the spots with h = even in the [010] zone axis diffraction patterns of Zn and Ni doped compounds [16]. This means that the substitutions of Cu ions either by nonmagnetic Zn 2+ ions or by weak magnetic Ni 2+ ions do not induce any changes in the structure of the compound.…”
Section: Structural Transition With the Co Dopingmentioning
confidence: 96%
“…It was also found that the (h02) C spots with h = odd remain stronger than the spots with h = even in the [010] zone axis diffraction patterns of Zn and Ni doped compounds [16]. This means that the substitutions of Cu ions either by nonmagnetic Zn 2+ ions or by weak magnetic Ni 2+ ions do not induce any changes in the structure of the compound.…”
Section: Structural Transition With the Co Dopingmentioning
confidence: 96%
“…This technology holds immense potential in the field of biomedicine and is expected to be used in high-throughput drug screening, new drug development, and biophysiological research. [126] Currently, organ-on-achip systems have been developed using cardiomyocytes and skeletal muscle cells.…”
Section: Organ-on-a-chipmentioning
confidence: 99%
“…A key to developing in vitro 3D cell models is the capacity to replicate the extracellular matrix (ECM) of the native tissue with respect to mechanical and chemical properties. [9,10] Hydrogels, which are polymer-based structures containing a large fraction of water, offer a valuable tool to recreate human physiology in ways not possible with traditional cell culture substrates. [11] The recent development of synthetic and hybrid polymers has overcome the batch-tobatch variation of natural hydrogels with maintained cell responsive functionalities combined with mechanical stability and good processability.…”
Section: Introductionmentioning
confidence: 99%